Editorial - Michael Kleinaltenkamp (jbm - Journal of Business Market Management, 2014)
It is a great pleasure to introduce you to the new format of jbm. After having been established as an Open Access Journal for several years now, the Journal's Editorial Advisory Board concluded that the journal is ready to take the next step in its development. Starting with this issue, the journal will be re-structured into the four sections: Classic, Thought Leadership, Case Studies and Methodologies and Replications and Extensions.
urn:nbn:de:0114-jbm-v7i1.820
Keywords: 650